2019
DOI: 10.1371/journal.pone.0227033
|View full text |Cite
|
Sign up to set email alerts
|

Modeling succinate dehydrogenase loss disorders in C. elegans through effects on hypoxia-inducible factor

Abstract: Mitochondrial disorders arise from defects in nuclear genes encoding enzymes of oxidative metabolism. Mutations of metabolic enzymes in somatic tissues can cause cancers due to oncometabolite accumulation. Paraganglioma and pheochromocytoma are examples, whose etiology and therapy are complicated by the absence of representative cell lines or animal models. These tumors can be driven by loss of the tricarboxylic acid cycle enzyme succinate dehydrogenase. We exploit the relationship between succinate accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Succinate accumulation, damaged oxygen consumption [ 83 , 84 ] Cell-specific sdhb-1(RNAi) C. elegans Cell-specific sdhb-1(RNAi) Also used DMOG to suppress SDH. Crosses with HIF mutants [ 85 ] Copy of human mutation in SDHB C. elegans Arg244His point mutant (corresponding to Arg230His in human SDHB ) Succinate accumulation, damaged oxygen consumption, increased pyruvate and lactate levels, increased LDH activity. Sterile adults [ 84 ] mev-1 C. elegans G71E in SDHC mev-1 was discovered in a worm screen for oxygen sensitivity.…”
Section: Model Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinate accumulation, damaged oxygen consumption [ 83 , 84 ] Cell-specific sdhb-1(RNAi) C. elegans Cell-specific sdhb-1(RNAi) Also used DMOG to suppress SDH. Crosses with HIF mutants [ 85 ] Copy of human mutation in SDHB C. elegans Arg244His point mutant (corresponding to Arg230His in human SDHB ) Succinate accumulation, damaged oxygen consumption, increased pyruvate and lactate levels, increased LDH activity. Sterile adults [ 84 ] mev-1 C. elegans G71E in SDHC mev-1 was discovered in a worm screen for oxygen sensitivity.…”
Section: Model Systemsmentioning
confidence: 99%
“…Another worm group used convergent genetic and pharmacological approaches to study the effect of SDH deficits on the HIF system in the worm [ 85 ]. One effect of HIF activation in the worm is a delay in egg-laying, or ‘egg retention’.…”
Section: Model Systemsmentioning
confidence: 99%
“…Current hypotheses focus on the roles of accumulating succinate as an oncometabolite, augmented damage by reactive oxygen species (ROS), and hypersuccinylation ( Ishii et al 2005 , Selak et al 2005 , Smestad et al 2018 ). ROS production has been shown to increase in SDH loss model organisms, but it is unclear how much protein and DNA damage results ( Adachi et al 1998 , Ishii et al 2005 , Smith et al 2007 , Braun et al 2019 ). Recent work has shown that the loss of SDHB in particular disrupts iron homeostasis, leading to exacerbated ROS generation and hallmarks of the tumor phenotype such as pseudohypoxia and DNA hypermethylation.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to envision therapeutics and probe PGL mechanisms, several model systems, including Caenorhabditis elegans, zebrafish, rodents, mammalian cell lines, and the yeast Saccharomyces cerevisiae have been used in lieu of conventional cancer models (Bancos et al, 2013;Braun et al, 2019;Dona et al, 2021;Lussey-Lepoutre et al, 2018;Smestad et al, 2017;Smith et al, 2007). Yeast models of PGL have exploited the conserved mitochondrial role of SDH for studies of metabolic disorders (Bancos et al, 2013;Kregiel, 2012;Lussey-Lepoutre et al, 2018;Smith et al, 2007).…”
Section: Words Introductionmentioning
confidence: 99%
“…Current hypotheses focus on the roles of accumulating succinate as an oncometabolite, augmented damage by reactive oxygen species (ROS), and hypersuccinylation (Ishii et al, 2005;Selak et al, 2005;Smestad et al, 2018). ROS production has been shown to increase in SDH-loss model organsims, but it is unclear how much protein and DNA damage results (Adachi et al, 1998;Braun et al, 2019;Ishii et al, 2005;Smith et al, 2007). There is evidence that inherent oxidative stress enhances PGL sensitivity to additional oxidative damage (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%